Use of Self‐Assembled Monolayers for the Sequential and Independent Immobilisation of Enzymes. Issue 20 (14th October 2021) - Serleti, Alessandro; Xiao, Xinxin; Shortall, Kim; Magner, Edmond
Abstract: The precise spatial control of the immobilisation of enzymes is necessary for the sequential localisation of an enzymatic cascade. In this contribution, the sequential immobilisation of alcohol dehydrogenase (ADH), formaldehyde dehydrogenase (FLDH) and formate dehydrogenase (FoDH) on self‐assembled monolayer modified electrodes has been demonstrated. A range of thiols were screened and optimal enzymatic activity was obtained with thiols bearing ‐OH, a positively charged heterocyclic aromatic ring and ‐COOH for the immobilisation of ADH, FLDH and FoDH, respectively. Scanning of the applied potential was utilised to separately modify individual electrodes with the appropriate thiol and enzyme to deliver a three‐enzyme system with catalytically active enzyme. Immobilised ADH, FLDH and FoDH retained 46, 32 and 76 % of initial activity, respectively, on storage in aqueous solution at 4 °C for a period of two weeks. Abstract : An electrochemically assisted "block and unblock" procedure is employed to immobilise three enzymes (alcohol dehydrogenase, formaldehyde dehydrogenase and formate dehydrogenase) sequentially and independently at three individual gold electrodes.